Evaluation of pH, buffering capacity, viscosity and flow rate levels of saliva in caries-free, minimal caries and nursing caries children: An in vivo study - Animireddy, Dwitha; Reddy Bekkem, VenkataThimma; Vallala, Pranitha; Kotha, SunilBabu; Ankireddy, Swetha; Mohammad, Noorjahan (Contemporary clinical dentistry, 2014)
The present study was undertaken to evaluate the pH, buffering capacity, viscosity and flow rate of saliva in caries free, minimal caries and nursing caries children and to evaluate the relationship of these on the caries activity of children. A total of 75 school children of age group between 4 and 12 years were selected and divided into three equal groups: Group I, Group II and Group III, consisting of 25 subjects each. Group I included caries-free subjects, Group II included subjects with minimal caries and Group III included subjects with nursing caries. Saliva samples were collected from all subjects and were estimated for flow rate, pH, buffering capacity and viscosity. There was a significant decrease in the mean salivary flow rate, salivary ph and salivary buffer capacity and a significant increase in the salivary viscosity among caries-free subjects, subjects with minimal caries and subjects with nursing caries. The physicochemical properties of saliva, such as salivary flow rate, pH, buffering capacity and viscosity, has a relation with caries activity in children and act as markers of caries activity.